What Do Spelling Errors Tell Us about Deaf Learners of French?. (20th January 2020) - Daigle, Daniel; Berthiaume, Rachel; Costerg, Agnès; Plisson, Anne
Abstract: For deaf students, spelling acquisition is a considerable challenge, especially because the spelling code is based on an oral language to which most of them have limited access. Most studies conducted with deaf students have reported that they lag behind their hearing peers. However, few studies have used a fine-grained error classification grid. The use of such a grid makes it possible to draw a precise portrait of writers' orthographic knowledge. The purpose of this study was to describe the spelling skills of 19 deaf students ( M age = 10.9 years) and to compare their errors with those of 20 hearing students of the same age and 17 younger hearing students at the same reading level. The results indicate that deaf students are not quantitatively different from hearing students but that their errors are qualitatively different from those of hearing students.